2022
DOI: 10.3390/antiox11081613
|View full text |Cite
|
Sign up to set email alerts
|

Hormesis and Oxidative Distress: Pathophysiology of Reactive Oxygen Species and the Open Question of Antioxidant Modulation and Supplementation

Abstract: Alterations of redox homeostasis leads to a condition of resilience known as hormesis that is due to the activation of redox-sensitive pathways stimulating cell proliferation, growth, differentiation, and angiogenesis. Instead, supraphysiological production of reactive oxygen species (ROS) exceeds antioxidant defence and leads to oxidative distress. This condition induces damage to biomolecules and is responsible or co-responsible for the onset of several chronic pathologies. Thus, a dietary antioxidant supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 311 publications
0
14
0
Order By: Relevance
“…The pathogenesis of several human diseases including cancer is characterised by alterations of intracellular redox homeostasis [Traverso N, Ricciarelli R et al 2013;Nitti M, Marengo B et al 2022].…”
Section: Role Of Gsh In Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…The pathogenesis of several human diseases including cancer is characterised by alterations of intracellular redox homeostasis [Traverso N, Ricciarelli R et al 2013;Nitti M, Marengo B et al 2022].…”
Section: Role Of Gsh In Cancermentioning
confidence: 99%
“…Although cancer cells prefer aerobic glycolysis (Warburg effect), in order to satisfy their energy demands, under pro-oxidant conditions their metabolism can shift towards oxidative phosphorylation (OXPHOS), that is a dynamic and reversible process strongly involved in cancer progression and therapy resistance [Nitti M, Marengo B et al 2022]. In this connection, our recent study demonstrated that the inhibition of protein kinase C- (PKC-), by favouring the switch from OXPHOS to aerobic glycolysis, is able to reduce GSH levels and stimulate ferroptosis (see next paragraph) of chemoresistant neuroblastoma stem cells [Monteleone L, Speciale A et al 2021].…”
Section: Role Of Gsh In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…To reconcile both deleterious and physiological aspects of ROS, Sies and Jones [ 30 ] defined OS as an imbalance between reactive oxidative species or ROS and antioxidants in favor of the formers, leading to a signaling disruption as a consequence of oxidative damages to lipids, and DNA evidenced by the measurement of proteins. A third interesting and novel concept is adaptive oxidative stress or hormesis ( Figure 1 ) defined as a phenomenon in which ROS produced in moderate amounts had beneficial effects to living organisms [ 31 , 32 , 33 ].…”
Section: Oxidative Stress Definitionsmentioning
confidence: 99%
“…If these products undergo certain modifications and thereby stabilize, they are converted into advanced glycation endproducts (AGEs) (Semchyshyn, 2013). Both Maillard products and AGEs are capable of inducing oxidative stress (Hegele et al, 2009;Nitti et al, 2022;Schmitt et al, 2006;Van Nguyen, 2006b). Oxidative stress results in tissue damage and accelerates aging (Liguori et al, 2018).…”
Section: Introductionmentioning
confidence: 99%